Inhibition of Escherichia coli in Fruit Juices by Pulsed Electric Fields. - กันทะลา, ชัชวาลย์; วงค์จันทร์แก้ว, นิติกร; อินต๊ะ, พานิช; รัตนเดโช, ผดุงศักดิ์ (RMUTL Engineering Journal, 2017)
This work studies the inhibition of bacteria, E. coli, in orange and guava juice by pulse electric field. The experiment was done by inoculating E. coli into 106 CFU/ml of orange and guava juice. The inhibition of E. coli growth was measured after applying 20 kV/cm pulsed electric field strength with the frequency of 1 Hz at five pulse numbers including 500, 600, 700, 800 and 900 pulses, respectively. Total bacteria plate count was performed by using a non-selective growth technique by culturing the bacteria on nutrient agar before incubating at 37oC for 24 hrs, after which the initial and surviving number cells were measured. The results show that PEF inhibited the inoculated bacteria in both of juices about 6 logarithmic at the frequency of 1 Hz with pulse number greater than 600 pulses.